Numerous Overlapping Programs Add Complexity, Unpredictability to Rural Hospital Finances - Carolyn San Soucie; Michael E Chernew; Benjamin D Sommers (Health Affairs Scholar, 2026)
Abstract Introduction Rural hospitals face unique financial challenges, prompting Congressional action including multiple Medicare-specific payment programs. Medicare’s programs to enhance rural hospital payment include: Critical Access, Sole Community, Medicare-Dependent, and Low-Volume Hospitals. Methods We examined the payments made through these programs and their resulting impact on hospitals’ finances for 2,942 rural hospitals from 1997 to 2024 using cost report data. Results Almost four-fifths (82.4%) of rural hospitals received payment from one of the programs. From 2015 to 2024, 14.7% of participating hospitals churned between programs. In 34.6% of hospital-years, hospitals received no special payments from programs they were eligible for. Furthermore, payments received by SCHs and MDHs fluctuated by more than 50% year-to-year for 16.0% of hospital-years. Financial reliance on these programs was larger in states that have not expanded Medicaid and for hospitals participating in two programs simultaneously. Conclusion Overall, many rural hospitals rely on Medicare’s special payment programs, but funding unpredictability, complicated and overlapping eligibility rules, and payment formulas based on historic costs create challenges for hospitals’ finances. There is a need to streamline Medicare payment and make existing programs more efficient before layering on dozens of differing state-level policies through the recently created Rural Health Transformation Program.